Imaging-driven diagnosis of retroperitoneal psoas major alveolar soft part sarcoma: a case report - Wei, Shasha; He, Ming; Li, Wenfu; Liu, Lin; Fan, Guang Ming (Frontiers in Oncology, 2025)
Alveolar soft part sarcoma (ASPS) is an infrequent and malignant soft tissue tumor with an elusive tissue origin. Its occurrence in the retroperitoneal psoas major muscle is extremely rare. The tumor’s deep retroperitoneal location, complex anatomy, and hypervascularity pose challenges to preoperative diagnosis and surgical intervention. This case report presents a 21-year-old female diagnosed with left retroperitoneal psoas major ASPS. Advanced imaging modalities, such as computed tomography (CT) multidirectional reconstruction, magnetic resonance imaging (MRI), and three-dimensional (3D) rendering, were utilized. These imaging techniques not only clearly depicted the tumor’s characteristics but also its spatial relationships with surrounding tissues and the vascular network. The detailed preoperative vascular assessment enabled the surgical team to comprehend the tumor anatomy and meticulously plan the approach, thus significantly reducing surgical risks and potential complications. The procedures and outcomes of this case offer valuable insights for clinical practice, highlighting the crucial role of imaging in the diagnosis and treatment of rare ASPS cases.